Novel amino acid‐based surfactant for silicone emulsification and its application in hair care products: a promising alternative to quaternary ammonium cationic surfactants. (15th August 2017) - Fujii, M.; Inoue, M.; Fukami, T.
Abstract: Objective: Quaternary ammonium cationic surfactants (ACSs) and N‐[3‐alkyl(12, 14)oxy‐2‐hydroxypropyl]‐l ‐arginine hydrochloride (N‐AOHPA) were used to emulsify silicone. The potential of the resulting emulsions in hair conditioning products was investigated. Methods: The emulsions were prepared using a homogenizer and/or high‐pressure homogenizer. ACSs and N‐AOHPA were used as silicone emulsifiers. The stability of the emulsions was evaluated by measuring particle sizes, creaming fractions, polydispersity indexes and zeta potentials. Moreover, the N‐AOHPA‐stabilized emulsion was compared with the ACS‐stabilized emulsion to evaluate the adsorption amount of silicone on healthy and bleached hair surfaces and the inhibitory effects on amino acid dissolution from bleached hair. The adsorption site of the N‐AOHPA‐stabilized emulsion was observed using a scanning electron microscope. Results: For all surfactants, the silicone emulsions prepared using the high‐pressure homogenizer were more stable than those prepared using the homogenizer. When N‐AOHPA was used as the surfactant, the silicone emulsion was especially stable. Furthermore, the d50 value of the N‐AOHPA‐stabilized emulsion was smaller than that of the ACS‐stabilized emulsion. The adsorption behaviour of the silicone droplets in the different emulsions varied depending on the nature of the surfactant and the preparation method. The amount of ACS‐stabilized silicone adsorbed on healthy hair was higher than that adsorbed on bleached hair, especially when the emulsion was prepared using the homogenizer. In contrast, the amount of N‐AOHPA‐stabilized silicone adsorbed on bleached hair was high, and no differences were observed between the N‐AOHPA‐stabilized emulsions prepared using the homogenizer and high‐pressure homogenizer. The emulsified droplets, especially the N‐AOHPA‐stabilized droplets prepared using the high‐pressure homogenizer, prevented amino acid dissolution from bleached hair. It was concluded that the silicone droplet adsorption site affected the dissolution process because the small N‐AOHPA‐stabilized droplets adsorbed at cuticle edges. Conclusion: This study shows that N‐AOHPA has good potential for use as an emulsifier in products used for improving the condition of damaged hair. Abstract : Schematic diagram of adsorption behavior of macro size (HME) and nano size (HPHE) of silicone dloplets.